Strong Electron Correlation in Cu-doped CaO Nanocolloid - Trang, Nguyen Thuy; Nhat, Hoang Nam (Communications in Physics, 2016)
Theoretical prediction of magnetism induced by defects or doping in non-metallic colloids has gained a renewed interests recently. In this work, we investigated the possible appearance of magnetism in Cu doped CaO nanocolloids activated by SPAN-80 in the framework of density functional theory (DFT). Despite of strong antiferromagnetic superexchange interaction between Cu$^{2 + }$ ions, the local magnetic moment of Cu may arise due to attachment of colloidal agent onto the surface of CaO nanocluster. The ferromagnetism attributes to the degeneration of Cu 3d orbitals in CaO crystal fields, the aspects of electron correlation and quantum spin fluctuation. %PACS number: 42.30.R, 42.40.Ht, 42.30.Kq